TOPIK PENELITIAN TERKINI SEPUTAR PASAR MODAL SYARIAH - Yuliana, Rita (InFestasi, 2019)
This article aims to present recent issues from research topics regarding Islamic capital market. This presentation accompanied with explanation regarding condition and development of Islamic capital market in Indonesia. It is essential to provide understanding that Islamic capital market research can be done as the data needed is adequate and easy to obtain. This article use reference from reputable international journals, while journal from Indonesia can’t be included since the limitation of reputable journal that discuss about Islamic capital market. Result from this article can be used to provide contribution in theory, practice, and policy.